Role Organizational Culture towards Employee Engagement in The Context of Green Economy in Technology Companies Multinational Studies Google LLC Case: JEL Classification: M14, M12, M54, Q56, F23 - Serlin Serang; Suriyanti Suriyanti; Albani Mukti Adrias; Sela Mita Permata Sari (Newinera Publisher, 2026)
This study aims to examine the role of organizational culture in shaping employee engagement within the context of the green economy in multinational technology companies, with Google LLC used as an illustrative case. Adopting a qualitative approach through a systematic literature review, this research synthesizes theoretical frameworks and empirical findings related to organizational culture, employee engagement, and sustainability-oriented organizational practices. The analysis draws on reputable academic books and peer-reviewed journal articles to explore how shared values, norms, and meanings embedded in organizational culture influence employees’ psychological attachment, motivation, and involvement at work. The findings indicate that organizational culture plays a fundamental role in fostering employee engagement by creating a supportive environment that enhances vigor, dedication, and absorption. Furthermore, the integration of green economy principles into organizational culture strengthens employees’ sense of meaningful work, collective identity, and emotional attachment to the organization. In the context of multinational technology companies, sustainability-oriented cultural values not only support environmental responsibility but also contribute to long-term employee engagement and talent retention. This study contributes conceptually by positioning the green economy as a contextual factor that reinforces the relationship between organizational culture and employee engagement, offering insights for sustainable human resource management and organizational development.